The Impact of Transformational Leadership on Teacher Performance and Student Achievement in Secondary Schools - Pajar Machmud; Shirley A. Padua; Alvin S. Sicat (Yayasan Putra Adi Dharma, 2024)
This study explores the influence of transformational leadership on teacher performance and student achievement in secondary schools. By examining the relationship between transformational leadership practices and educational outcomes, the research aims to provide insights into effective leadership strategies that enhance both teacher efficacy and student success. Employing a mixed-methods approach, the study integrates quantitative and qualitative data to offer a comprehensive understanding of the impact of transformational leadership in educational settings. The findings reveal significant positive correlations between transformational leadership, teacher performance, and student achievement, underscoring the importance of fostering leadership qualities that inspire, motivate, and support teachers and students